2003
DOI: 10.1097/00003246-200301000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium between tumor necrosis factor (TNF)-α–308 G/A promoter and TNF-βNco I polymorphisms: Association with TNF-α response of granulocytes to endotoxin stimulation

Abstract: A linkage disequilibrium between the two TNF polymorphisms was found. This study revealed a significant association between genotype and phenotype for both TNF polymorphisms. Heterozygosity for both TNF polymorphisms is associated with an increased TNF-alpha response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 24 publications
4
28
2
1
Order By: Relevance
“…The allele frequencies found in our study for the three TNF polymorphisms were in agreement with those reported in previous studies (11,16 ). We also demonstrated that the Ϫ863 C/A polymorphism is associated with the TNF-␣ response of human whole blood of healthy volunteers to endotoxin stimulation.…”
Section: Rapid Genotyping For Tumor Necrosis Factor-␣ (Tnf-␣)supporting
confidence: 92%
See 1 more Smart Citation
“…The allele frequencies found in our study for the three TNF polymorphisms were in agreement with those reported in previous studies (11,16 ). We also demonstrated that the Ϫ863 C/A polymorphism is associated with the TNF-␣ response of human whole blood of healthy volunteers to endotoxin stimulation.…”
Section: Rapid Genotyping For Tumor Necrosis Factor-␣ (Tnf-␣)supporting
confidence: 92%
“…Genotyping for the TNF-␣ Ϫ308 and the LTA NcoI genetic polymorphisms was carried out as described previously (16 ). Because a previously described assay for genotyping for the TNF-␣ Ϫ863 polymorphism (11 ) is time-consuming and requires several manual steps, we developed a real-time PCR assay with specific fluorescently labeled hybridization probes.…”
Section: Rapid Genotyping For Tumor Necrosis Factor-␣ (Tnf-␣)mentioning
confidence: 99%
“…18,23,40,58,63,66 When associations of individual SNPs among the TNF and LTA alleles were examined in this study, only a single association was observed. In each of the alleles described, the LTA SNP À293A was always found in association with LTA þ 81A and LTA þ 369C, while the LTA SNP À293G was always found associated with LTA þ 81C and LTA þ 369G.…”
Section: Discussionmentioning
confidence: 85%
“…For example, an association could be assigned between the SNPs TNF À308A, LTA þ 253G (NcoI RFLP; TNFB*1) and LTA þ 724A, which has been observed by others. 23,25,27,28,40 Interestingly, each of these SNPs generally have been associated with higher production level phenotypes of both TNF and LTA, with the 8.1 ancestral HLA haplotype …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation